(untitled) (CIPEEX, 2025)
Legal security is crucial in rural property purchase and sale contracts, ensuring that transactions are conducted legitimately and reliably, safeguarding the rights and duties of all parties involved. This summary highlights the key aspects of legal security in these contracts, emphasizing its importance and the elements that ensure legal compliance in transactions. The study involved document analysis, participation in online congresses, and a review of current legislation to identify the legal requirements and necessary precautions. The findings reveal that acquiring rural property demands several safeguards to ensure the success of the transaction. Transparency between parties is essential, requiring verification of property documentation, such as registration, negative certificates, and compliance with environmental standards. According to Article 108 of the 2002 Civil Code, a public deed is mandatory for the validity of legal transactions. The contract must also be drafted in line with current legislation, explicitly addressing the regulations governing property sales. In conclusion, legal security in rural property contracts is indispensable for protecting the interests of buyers and sellers. By adhering to legal requirements and ensuring proper documentation, risks can be minimized, enabling safe and efficient transactions.